Practical challenges in the conduct of pragmatic trials embedded in health plans: Lessons of IMPACT-AFib, an FDA-Catalyst trial. (August 2020) - Garcia, Crystal J; Haynes, Kevin; Pokorney, Sean D; Lin, Nancy D; McMahill-Walraven, Cheryl; Nair, Vinit; Parlett, Lauren; Martin, David; Al-Khalidi, Hussein R; McCall, Debbe; Granger, Christopher B; Platt, Richard; et al.
IMPACT-AFib was an 80, 000-patient randomized clinical trial implemented by five US insurance companies (health plans) aimed at increasing the use of oral anticoagulants by individuals with atrial fibrillation who were at high risk of stroke and not on treatment. The underlying thesis was that patients could be change agents to initiate prescribing discussions with their providers. We tested the effect of mailing information to both patients and their providers. We used administrative medical claims and pharmacy dispensing data to identify eligible patients, to randomize them to an early or delayed intervention, and to assess clinical outcomes. The core data were analysis-ready datasets each site had created and curated for the FDA's Sentinel System, supplemented by updated "fresh" pharmacy and enrollment data to ensure eligibility at the time of intervention. Following mutually agreed upon procedures, sites linked to additional internal source data to implement the intervention—educational information mailed to patients and their providers in the early intervention arm, and to providers of patients in the delayed intervention arm approximately 12 months later. The primary analysis compares the early intervention arm to the delayed intervention arm, prior to the delayed intervention being conducted (i.e. compares intervention to non-intervention). The endpoints of interest were evidence of initiation of anticoagulation (primary) as well as clinical endpoints, including stroke and hospitalization for bleeding. Major challenges, some unanticipated, identified during the planning phase include convening multi-stakeholder investigator teams and advisors, addressing ethical concerns about not intervening in a usual care comparison group, and identifying and avoiding interference with sites' routine programs that were similar to the intervention. Needs and challenges during the implementation phase included the fact that even limited site-specific programming greatly increased time and effort, the need to refresh research data extracts immediately before outreach to patients and providers, potential difficulty identifying low-cost medications such as warfarin that may not be reimbursed by health plans and so not discoverable in dispensing data, the need to develop workarounds when "providers" in claims data were facilities, difficulty addressing clustering of patients by provider because providers can have multiple identifiers within and between health plans, and the need to anticipate loss to follow up because of health plan disenrollment or change in benefits. As pragmatic trials begin to shape evidence generation within clinical practice, investigators should anticipate issues inherent to claims data and working with multiple large sites. In IMPACT-AFib, we found that investing in collaboration and communication among all parties throughout all phases of the study helped ensure common understanding, early identification of challenges, and streamlined actual implementation.